Bi-functional sulphonate-coupled reduced graphene oxide as an efficient dopant for a conducting polymer with enhanced electrochemical performance - Meng, Lingyin; Dagsgård, Frida; Turner, Anthony P. F.; Mak, Wing Cheung (Royal Society of Chemistry, 2020)
The rapidly emerging field of organic bioelectronics has witnessed the wide use of conducting polymers (CPs) to fabricate advanced chemically modified electrodes (CMEs) for biosensors and biomedical devices. The electrochemical performance of the CPs in such devices is closely related to the quality and physiochemical nature of the dopants. A bi-functional graphene oxide derivative with high reduction degree and negatively-charged sulphonate functionality, i.e. sulphonate-coupled reduced graphene oxide (S-RGO), was developed and used as an efficient dopant for a CP with enhanced electrochemical performance. The S-RGO was synthesised via a facile one-pot hydrothermal reaction using 4-hydrazinobenzosulphonic acid (4-HBS) as reductant and sulphonate precursor simultaneously. The resulting S-RGO possesses high aqueous dispersion stability (more than 6 months), high electrical conductivity (1493.0 S m−1) and sulphonate functionality. Due to these specific properties, S-RGO demonstrated improved electropolymerisation efficiency for poly(3,4-ethylenedioxythiophene) (PEDOT) proving an effective dopant for the preparation of a PEDOT:S-RGO film (5 mC) with faster polymerisation time (37 s) compared to the conventional 2D dopants GO (PEDOT:GO, 129 s) and RGO (PEDOT:RGO, 66 s). The resulting PEDOT:S-RGO appeared as a homogenous film with uniformly distributed S-RGO dopant, low equivalent series resistance and low charge transfer resistance. Moreover, the electrochemical transduction performance of the PEDOT:S-RGO interface was evaluated with 4 different analytes, including ferric/ferrocyanide redox probe, dopamine, nicotinamide adenine dinucleotide and hydrogen peroxide. As a result of the synergistic effect of S-RGO and PEDOT, the PEDOT:S-RGO demonstrated enhanced electrochemical performance with respect to faster electrode kinetics (smaller ΔEp), ∼2 and ∼4 times increased current responses, and lower peak potentials compared to PEDOT:GO and PEDOT:RGO. This bi-functional S-RGO dopant combined the advantages of conventional GO and RGO to deliver sulphonate functionality and high conductivity for the preparation of advanced PEDOT interface with improved electrochemical performance, that could potentially be applied for applications in electrochemical sensors, biosensors and bioelectronic devices